New insights on the convective and microphysical characteristics of heavyrainfallin monsoon coastalareas (South China) (MAUSAM, 2026)
During the past three years, new insights have been gained into the convective features andmicrophysical characteristics of heavy rainfall in South China, which is a typical monsoon coastal area. Such improvedunderstanding is closely related to the rapid progress of application of advanced remote sensing techniques, in particularthe upgrade of the dual-polarization function of the operational weather radars in South China. This paper reviews therepresentative studies since approximately 2019 in three aspects. First, spatiotemporal distribution and diurnalpropagation of the convection initiation during the warm season. Second, general features and synoptic-scaleenvironments of the meso-beta-scale convective systems (MCSs) during the pre-summer rainy season (April to June). Third,microphysical characteristics of the extreme short-term rainfall and the coexisting frontal and warm-sector heavy rainfallin South China.